A near miss: an uncommon injury following a common mechanism. (5th August 2011) - Bryson, David; Khan, Zeeshan; Aujla, Randeep; Bromage, James David
Abstract : Subtalar dislocation is an uncommon injury involving the simultaneous dislocation of the talocalcaneal and talonavicular joints. Radiographic images can be difficult to interpret for the inexperienced clinician because of the obliquity of the foot and the overlap of tarsal bones. The authors describe the case of a 24-year-old male who presented to the emergency department (ED) with a painful left foot and ankle following a twisting injury. He was examined by a junior member of the ED team and diagnosed with a left ankle sprain. Preparations were underway for discharge home when the radiographs, described as 'normal but somewhat strange', were shown to the orthopaedic senior house officer who happened to be in the ED. The patient was subsequently reviewed by the orthopaedic registrar and diagnosed with a medial subtalar dislocation. He was then taken to theatre for closed reduction and application of a below-knee cast.